The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
DOI: 10.31274/rtd-180817-1976
|View full text |Cite
|
Sign up to set email alerts
|

Entomogenous fungi of corn insects in Iowa

Abstract: Signature was redacted for privacy.Signature was redacted for privacy.Signature was redacted for privacy. 3 13 31 72 73 74 80 81

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…There are numerous reports of inflammatory responses in insects to microsporidia (Brooks 1988). Melanized spores of Nosema stegomyiae have been reported only in adult Aedes aegypti (Marchoux et al 1903) while melanized spores of Brachiola algerae have been found in both larvae and adults of Anopheles stephensi and A. aegypti (Vávra and Undeen 1970).…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous reports of inflammatory responses in insects to microsporidia (Brooks 1988). Melanized spores of Nosema stegomyiae have been reported only in adult Aedes aegypti (Marchoux et al 1903) while melanized spores of Brachiola algerae have been found in both larvae and adults of Anopheles stephensi and A. aegypti (Vávra and Undeen 1970).…”
Section: Discussionmentioning
confidence: 99%
“…Ostrinia nubilalis Iowa (USA) dead adult and larva [22] Schistocerca gregaria Egypt dead adult [23] Spodoptera littoralis Egypt eggs [24] Triatoma brasiliensis Brazil digestive tract [25] P. brasilianum unidentified insect South Korea dead insect [26] P. brevicompactum…”
Section: P Aurantiogriseummentioning
confidence: 99%
“…Brazil adult [32] H. hempei Mexico cuticle and gut of females [30] Nomia melanderi western USA diseased larva [41] Parastrongylus megistus Brazil digestive tract [42] Pteroptyx bearni Sabah (Malaysia) eggs [43] T. brasiliensis, T. infestans Brazil digestive tract [25] Triplectides sp. Brazil gut [20] unspecified insect Brazil internal mycobiota [19] V Helicoverpa zea Iowa (USA) dead larva and pupa [22] Ostrinia nubilalis Iowa (USA) dead larva [22] P. megistus Brazil digestive tract [42] T. brasiliensis Brazil digestive tract [25] V C. quinquefasciatus Thailand dead adult [40] Diaphania (Margaronia) pyloalis Japan larva [61] Euops lespedezae Japan mycangia [62] F. polyctena Poland workers [55] Halictus rubicundus India frass [63] Lasioglossum zephyrum India dead larvae [63] Lixus impressiventris South Korea dead insect [54] M. domestica Iran adults [64] M. domestica Brazil diseased adult/larva [36] Periplaneta americana Sumatra (Indonesia) adult [65] Table 1. Cont.…”
Section: Aedes Aegyptimentioning
confidence: 99%
“…-In a coming paper Bjorkman (1948) shows that these differences obviously are due to thf tad that older cultures endure tiigher temperatures less than newly isolated strains of PUacidiuni (private commiuiication). r 2.…”
Section: The Influence Of Temperature On the Growth Rate Of The Fungusmentioning
confidence: 97%